2018
DOI: 10.1021/acsami.8b04419
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nanosized Defective Lithium Peroxides through Si-Coated Carbon Nanotube Cathodes for High Energy Efficiency Li–O2 Batteries

Abstract: The formation and decomposition of lithium peroxides (LiO) during cycling is the key process for the reversible operation of lithium-oxygen batteries. The manipulation of such products from the large toroidal particles about hundreds of nanometers to the ones in the scale of tens of nanometers can improve the energy efficiency and the cycle life of the batteries. In this work, we carry out an in situ morphology tuning of LiO by virtue of the surface properties of the n-type Si-modified aligned carbon nanotube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In this way, Li 2 O 2 decomposition could be facilitated and the charge overpotential could be lowered. [ 40 ]…”
Section: Li2o2‐related Electrochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, Li 2 O 2 decomposition could be facilitated and the charge overpotential could be lowered. [ 40 ]…”
Section: Li2o2‐related Electrochemistrymentioning
confidence: 99%
“…For example, Guo and co‐workers fabricated a heavy n‐type Si coating layer onto aligned carbon nanotube (CNT) cathodes. [ 40 ] With the addition of such a layer on the CNT cathode surface, the discharge product featured a nanoparticle morphology (10–20 nm). The crystallinity was quite low with plenty of lithium vacancies.…”
Section: Strategies To Control Li2o2 Structure/morphologymentioning
confidence: 99%
“…For example, a magnetron sputtering n-type Si nanoparticle on CNT composite positive electrode presented discharge product in the form of low crystalline accompanied with large amounts of defects and vacancies inside, which was in a striking contrast to the large toroid products formed on the bare CNT surface. Furthermore, the side reactions were inhibited by the Si coating, resulting in ultra-low cycling voltage gap of 0.72 V. While for the pristine CNT positive electrode, the gap was increased to 1.7 V under the same testing condition of 0.1 mA•cm −2 (Figure 6d,e) [117]. The battery with a highly ordered hierarchically porous honeycomb-like structured carbon skeleton could work under an ultrahigh discharging rate because of the greatly enhanced mass transfer.…”
Section: Composite With Carbonmentioning
confidence: 97%
“…The computed adsorption energy indicated that LiO 2 was more favorably adsorbed at the interface of ZnO/VACNT than Li 2 O 2 and Li 3 O 4 ; thus, further disproportionation was inhibited. Several reports have shown that the formation of Li 2− x O 2 can be induced by using semiconducting catalysts, but similarly, no mechanism with concrete evidence has been proposed . Thus, more research is required to develop a clearer understanding of the function and catalytic mechanism of semiconductors in Li–O 2 batteries.…”
Section: Induced Defects In Li2o2mentioning
confidence: 99%
“…Several reports have shown that the formation of Li 2−x O 2 can be induced by using semiconducting catalysts, but similarly, no mechanism with concrete evidence has been proposed. [73,77] Thus, more research is required to develop a clearer understanding of the function and catalytic mechanism of semiconductors in Li-O 2 batteries.…”
Section: Li-deficient LI 2 Omentioning
confidence: 99%